Docking and subduction of the West Pacific seamounts along the Mariana Trench and their effects. (4th March 2016) - Zhang, Bin; Li, Guangxue; Li, Sanzhong; Dada, Olusegun A.
Abstract: The Mariana Trench is located at the edge of the West Pacific Plate, with a lot of large aseismic ridges lying there. These seamounts significantly affect the trench morphology and topographic change by the continuous subduction associated with NW‐directed Pacific Plate motion. In this article, the topography of the Mariana Trench is analysed by considering the free‐space and Bouguer‐gravity anomalies and the interaction between the seamounts and the plate boundary. All results indicate that following the movement of relatively isolated large‐sized seamounts near the plate boundary to the edge of the Mariana Trench, the impact of the subducting plate on the surrounding area lessens. As a consequence, the trench becomes shallower and jumps towards the seaward edge. Furthermore, a large area of large‐sized seamounts and oceanic rises will incise the subducting plate while approaching the trench axis, promote the subduction processes and increase the trench bathymetries. Shallower bathymetries at the middle section of the Mariana Trench, the discontinuous trench axes and some fickle topographic features in the front of the arc, are mostly caused by the docking or the subduction of the relatively isolated large‐scale seamounts. The docking or the subduction of a large area of seamounts has certain influences on the formation of a deep‐sea trench at the south section. Copyright © 2016 John Wiley & Sons, Ltd.